The role of active-site amino acid residues in the cleavage of DNA and RNA substrates by human apurinic/apyrimidinic endonuclease APE1 - Alekseeva, I.V.; Kuznetsova, A.A.; Bakman, A.S.; Fedorova, O.S.; Kuznetsov, N.A. (Biochimica et biophysica acta. General subjects, 2020)
Human apurinic/apyrimidinic endonuclease APE1 is one of participants of the DNA base excision repair pathway. APE1 processes AP-sites and many other types of DNA damage via hydrolysis of the phosphodiester bond on the 5′ side of the lesion. APE1 also acts as an endoribonuclease, i.e., can cleave undamaged RNA. Using pre-steady-state kinetic analysis we examined the role of certain catalytically important amino acids in APE1 enzymatic pathway and described their involvement in the mechanism of the target nucleotide recognition. Comparative analysis of the cleavage efficiency of damaged DNAs containing an abasic site, 5,6-dihydrouridine, or α-anomer of adenosine as well as 3′-5′-exonuclease degradation of undamaged DNA and endonuclease hydrolysis of RNA substrates by mutant APE1 enzymes containing a substitution of an active-site amino acid residue (D210N, N212A, T268D, M270A, or D308A) was performed. Detailed pre–steady-state kinetics of conformational changes of the enzyme and of DNA substrate molecules during recognition and cleavage of the abasic site were studied. It was revealed that substitution T268D significantly disturbed initial DNA binding, whereas Asn212 is critical for the DNA-bending stage and catalysis. Substitution D210N increased the binding efficacy and blocked the catalytic reaction, but D308A decreased the binding efficacy owing to disruption of Mg2+ coordination. Finally, the substitution of Met270 also destabilized the enzyme–substrate complex but did not affect the catalytic reaction. It was found that the tested substitutions of the active-site amino acid residues affected different stages of the complex formation process as well as the catalytic reaction. •Target nucleotide recognition and cleavage of a DNA or RNA by human APE1 was analyzed•Efficiency of enzymatic hydrolysis of different substrates was compared•Process of protein-substrate interaction was analyzed by pre-steady state kinetics•Conformational changes in APE1 and substrates were observed during their interactions•The role of certain important amino acids during enzyme pathway was specified